ANALYSIS OF STUDENTS INTERACTION NEEDS IN DISCUSSION ACTIVITIES AND ONLINE TUTORIAL ASSIGNMENTS - Pramudibyanto, Hascaryo; Bida, Obed; Maria Siwi, Cynthia (E-Journal of Cultural Studies, 2023)
As one of the services of online tutorial activities, this learning assistance service must also be able to provide interactive communication facilities between tutors and students. Achieving maximum value through this activity will be able to increase the acquisition of good final semester exam scores. The contribution of online tutorial grades can be obtained through students’ activeness in discussions and assignments. The basis for giving online tutorial grades is the results of submitting or uploading discussion responses in each online tutorial session with a minimum set of criteria. The problem of this study is the lack of feedback from tutors to students in online discussion forums. To address this issue, a descriptive method was used to identify and describe the consequences of not providing stimulus in the online tutorial discussion forum for the Sosiologi Komunikasi Massa course at the Open University during the 2022.1 registration period. The results of this study revealed the need for greeting messages and the availability of reminder facilities for students regarding tutor responses in discussion forums. Keywords: assignment grades, discussion responses, online tutorial, online tutorial